Konkurencyjny model funkcjonowania obszarów przyrodniczo cennych - Zielińska, Anetta (Competitive Model of Nature Valuable Areas Functioning, 2008)
Competitive model of nature valuable areas existing in the form of one macrospace interface will contribute to better running and managing the model of protecting valuable major ecosystems, bio- and landscape diversity in national, European and in global sense. To build such a model it must be taken into consideration: • building new legal, organizational and financial instruments, • creation of National Agency of Protected Areas, • elaborating plans for a protection of a model for the time not shorter than 20 years, • ecological education. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 38-44